Modulation of extracellular signal‐related kinase, cyclin D1, glial fibrillary acidic protein, and vimentin expression in estradiol‐pretreated astrocyte cultures treated with competence and progression growth factors. Issue 9 (6th June 2015) - Bramanti, Vincenzo; Grasso, Sonia; Tibullo, Daniele; Giallongo, Cesarina; Raciti, Giuseppina; Viola, Maria; Avola, Roberto
Abstract : The present study seeks to elucidate the interactions between the "competence" growth factor basic fibroblast growth factor (bFGF) and/or estrogen 17β‐estradiol and the "progression" growth factors epidermal growth factor (EGF), insulin‐like growth factor‐I (IGF‐I), and insulin (INS) on DNA labeling and also cyclin D1, extracellular signal‐related kinase 1/2 (ERK1/2), glial fibrillary acidic protein (GFAP), and vimentin expression in astroglial cultures under different experimental conditions. Pretreatment for 24 hr with bFGF and subsequent exposure for 36 hr to estradiol (E2 ) and EGF, IGF‐I, or INS stimulated DNA labeling in the last 12 hr, especially when the cultures were treated with progression growth factors. bFGF pretreatment and subsequent treatment with E2 for 36 hr stimulated DNA labeling. The 36‐hr E2 treatment alone did not significantly decrease DNA labeling, but contemporary addition of E2 with two or three growth factors stimulated DNA labeling remarkably. When E2 was coadded with growth factors, a significantly increased DNA labeling was observed, demonstrating an astroglial synergistic mitogenic effect evoked by contemporary treatment with growth factors in the presence of estrogens. Cyclin D1 expression was markedly increased when astrocyte cultures were pretreated for 36 hr with E2 and subsequently treated with two or three competence and progression growth factors. A highly significant increase of ERK1/2 expression was observed after all the treatments (EGF, bFGF, INS, IGF‐I alone or in combination with two or three growth factors). GFAP and vimentin expression was markedly increased when the cultures were treated with two or three growth factors. In conclusion, our data demonstrate estradiol–growth factor cross‐talk during astroglial cell proliferation and differentiation in culture. © 2015 Wiley Periodicals, Inc. Abstract : This study provides interesting evidence with regard to the intertwined dialogue between estrogens and growth factors in modulation of DNA labeling and some biomarker expressions during astroglial cell proliferation and differentiation. This interesting estrogens–growth factors cross‐talk may have significant implications for future therapeutic approachs to neurologic disorders associated with astrogliosis.